Kinesin and dynein superfamily proteins in organelle transport and cell division. - Hirokawa, N.; Noda, Y.; Okada, Y. (Current Opinion in Cell Biology, 1998)
Microtubule-associated motor proteins of the kinesin and dynein superfamilies play important roles in cellular mechanisms such as organelle transport and mitosis. Identification and characterization of new family members (in particular KIFC2, 16 new KIFs, XKlp2 and XKCM1 of the kinesin superfamily, and DHC2 and DHC3 of the dynein superfamily) and further characterization of known family members have improved our understanding of these cellular mechanisms. Sophisticated biophysical and structural analyses of monomeric and dimeric motor proteins have contributed to elucidating the mechanisms behind motor protein motility and polarity.